Geotourism and Climate Change: Paradoxes and Promises of Geotourism in Polar Regions - Hall, C.; Saarinen, Jarkko (Téoros, 2010)
Geotourism has achieved considerable prominence since the early 1990s as a means of conserving geological and geomorphological heritage. However, most accounts of the effects of geotourism are at a site-specific level while interpretation tends to focus on deep geological time rather than the Anthropocene. This restriction in consideration of time and space has meant that the broader effects of geotourism-related travel throughout the tourism system have been ignored, along with the potential role of climate change in affecting geosites and attractions. These issues are discussed with respect to the paradoxes of geotourism in polar regions with the polar cryospheric environment being both threatened by climate change yet simultaneously becoming more accessible and attractive to tourists. The article concludes that, like any form of tourism, geotourism needs to be understood within the broader context of tourism and physical systems rather than in isolation in order to fully access its contribution to geoconservation.